(untitled) (Research Bulletins of the Faculty of Economic Sciences, 2021)
The aim of this paper is to distinguish from other tax terminology public charges and to present the criteria for classification of taxes and their importance in the Polish tax system. Public tributes are a major source of Government revenue, and therefore an important aspect is to distinguish the characteristics of public charges, which determine their destiny on each task of the state.